Novel identification of the IRF7 region as an anticentromere autoantibody propensity locus in systemic sclerosis. Issue 1 (16th September 2011) - Carmona, F David; Gutala, Ramana; Simeón, Carmen P; Carreira, Patricia; Ortego-Centeno, Norberto; Vicente-Rabaneda, Esther; García-Hernández, Francisco J; García de la Peña, Paloma; Fernández-Castro, Mónica; Martínez-Estupiñán, Lina; Egurbide, María Victoria; Tsao, Betty P; et al.
Abstract : Objective: Systemic sclerosis (SSc) and systemic lupus erythematosus (SLE) are related chronic autoimmune diseases of complex aetiology in which the interferon (IFN) pathway plays a key role. Recent studies have reported an association between IRF7 and SLE which confers a risk to autoantibody production. A study was undertaken to investigate whether the IRF7 genomic region is also involved in susceptibility to SSc and the main clinical features. Methods: Two case-control sets of Caucasian origin from the USA and Spain, comprising a total of 2316 cases of SSc and 2347 healthy controls, were included in the study. Five single nucleotide polymorphisms (SNPs) in the PHRF1-IRF7-CDHR5 locus were genotyped using TaqMan allelic discrimination technology. A meta-analysis was performed to test the overall effect of these genetic variants on SSc. Results: Four out of five analysed SNPs were significantly associated with the presence of anticentromere autoantibodies (ACA) in the patients with SSc in the combined analysis (rs1131665: pFDR =6.14 × 10 −4, OR=0.78; rs4963128: pFDR =6.14 × 10 −4, OR=0.79; rs702966: pFDR =3.83 × 10 −3, OR=0.82; and rs2246614: pFDR =3.83 × 10 −3, OR=0.83). Significant p values were also obtained when the disease was tested globally; however, the statistical significance was lost when the ACA-positive patients were excluded from the study, suggesting that these associations rely on ACA positivity. Conditional logistic regression and allelic combination analyses suggested that the functional IRF7 SNP rs1131665 is the most likely causal variant. Conclusions: The results show that variation in the IRF7 genomic region is associated with the presence of ACA in patients with SSc, supporting other evidence that this locus represents a common risk factor for autoantibody production in autoimmune diseases.